2020
DOI: 10.3758/s13423-020-01721-y
|View full text |Cite
|
Sign up to set email alerts
|

Holistic but with reduced right-hemisphere involvement: The case of dyslexia in Chinese character recognition

Abstract: Recent research on visual object recognition has suggested that the right hemisphere can engage either holistic or part-based processing depending on whether the recognition relies on configural (exact distances among features) or featural information, respectively. Consistent with this finding, expert Chinese reading has been marked by a left-side bias (an indication of righthemisphere lateralization) with decreased holistic processing (as assessed using the composite paradigm) due to its reliance on featural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…The replicability of this exploratory analysis should be independently verified, but it is possible that weaknesses in reading are associated with greater left hemisphere lateralization of feature-based face processing. This could be consistent with a weaker left-side bias for Chinese character recognition of dyslexic readers in Hong Kong, likely indicating lessened right hemisphere lateralization/greater left hemisphere lateralization 106 . The authors suggest that dyslexic readers may not form appropriate part-based representations in the right hemisphere.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The replicability of this exploratory analysis should be independently verified, but it is possible that weaknesses in reading are associated with greater left hemisphere lateralization of feature-based face processing. This could be consistent with a weaker left-side bias for Chinese character recognition of dyslexic readers in Hong Kong, likely indicating lessened right hemisphere lateralization/greater left hemisphere lateralization 106 . The authors suggest that dyslexic readers may not form appropriate part-based representations in the right hemisphere.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Schmitt et al 122 report that dyslexic children, unlike controls, show no global-to-local interference in the Navon task which the authors interpret as an overreliance on analytic processing as opposed to holistic or global processing. Conversely, compared to typical readers, dyslexic readers showed signs of stronger holistic processing of English words 71 and Chinese characters 106 , 123 , and illiterates process both faces and houses more holistically compared to controls 124 . It is unclear whether these results are inconsistent with our findings of intact global form face processing in dyslexic readers.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although holistic processing is widely believed to be a general perceptual expertise marker across different domains that involve individualising within-category visual stimuli, several studies suggested the contrary. For example, expert Chinese character recognition is marked by reduced holistic processing (Chung et al, 2018 ; Liu et al, 2016 ), while novices (Hsiao & Cottrell, 2009 ; Tso et al, 2014 ) and Chinese readers with developmental dyslexia (Tso et al, 2020 , 2021 ) recognised Chinese characters with a stronger holistic effect. These findings are also in contrast to the previously observed reduced holistic processing effect associated with face recognition difficulties in the clinical population, such as patients with prosopagnosia (Avidan et al, 2011 ) or autism (Gauthier et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese orthography, a word retains its meaning even when the spacing between its components is altered, as long as its components and its first-order relationship (i.e., relative positions among character parts) remain unchanged. Tso et al (2020) suggested that featural information (e.g., individual strokes) played a more critical role in Chinese character recognition than did configural information (e.g., exact distances between strokes). Thus, the spatial information is crucial for processing individual musical notations and faces but not for Chinese characters (Ge et al, 2006).…”
Section: Introductionmentioning
confidence: 99%